Menuju Kesejahteraan Pesisir: Evaluasi Kebijakan Pembangunan Sosial Ekonomi Di Kecamatan Sape, Kabupaten Bima - Haeril Haeril (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
This research will focus on the evaluation of socio-economic development policies in Sape District, Bima Regency, with the aim of understanding the extent to which development efforts have achieved their goals. This study employs a qualitative descriptive method and a Literature Review. The research location includes the Bima Regency Development Planning Agency, the Department of Tourism, the Department of Marine and Fisheries, the Department of Environment, and the Department of Social Affairs of Bima Regency. The research findings indicate that Sape District has significant economic potential in the fisheries and agriculture sectors, but it still faces a considerable level of poverty, especially among coastal households. The economic empowerment of coastal communities needs to be enhanced through skills training programs, financial assistance for business capital, and improved access to business loans. Furthermore, a specific focus on generating employment opportunities, particularly for young people, is essential. Poor infrastructure and limited accessibility pose significant obstacles to economic development. Investments in infrastructure improvement, such as roads and ports, are required to enhance mobility and market access. Sustainable natural resource management is vital for preserving the potential of fisheries and agriculture in the area. Strict law enforcement against illegal fishing practices and educational efforts to promote sustainable fishing practices are necessary. Climate change impacts, including rising sea levels and extreme weather conditions, affect the region. Therefore, strategies for climate change adaptation and mitigation need to be developed. The evaluation of socio-economic development policies indicates that assistance programs have been implemented, but there is a need for improvement in directing policies toward poverty alleviation, economic empowerment, and sustainable natural resource management.